Household Demand for Financial Assets - Hamburger, Michael J. (Econometrica, 1968)
This paper investigates the household demand for four financial assets: marketable bonds, time and savings deposits at commercial banks, life insurance reserves, and savings accounts at other financial institutions-credit unions, savings and loan associations, and mutual savings banks. The focus of the analysis is on the substitution relationships among liquid assets, and between these assets and marketable securities. The explanatory variables used in the study are: income, wealth, and the yields on various assets included in household portfolios.